1999
DOI: 10.1210/en.140.10.4595
|View full text |Cite
|
Sign up to set email alerts
|

Biotin Regulation of Pancreatic Glucokinase and Insulin in Primary Cultured Rat Islets and in Biotin- Deficient Rats

Abstract: Biotin has been reported to affect glucose homeostasis; however, its role on pancreatic islets of Langerhans has not been assessed. In this report, we demonstrate that physiologic concentrations of biotin stimulate glucokinase activity in rat islets in culture. Using the branched DNA (bDNA) assay, a sensitive signal amplification technique, we detected relative increases in glucokinase mRNA levels of 41.5 +/- 13% and 81.3 +/- 19% at 12 and 24 h respectively in islets treated with [10(-6) M] biotin. Because glu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

11
40
1
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(53 citation statements)
references
References 0 publications
11
40
1
1
Order By: Relevance
“…A positive effect of biotin on insulin secretion has been reported (RomeroNavarro, G. et al 1999;Sone, H. et al 2000;Sone, H. et al 1999;Vilches-Flores, A. et al 2009). Studies by our group (Romero-Navarro, G. et al 1999;Vilches-Flores, A. et al 2009) and others (Sone, H. et al 2000;Sone, H. et al 1999) have revealed that glucose-stimulated insulin secretion increases in response to acute exposure to pharmacological doses of biotin in either primary cultured islets (Romero-Navarro, G. et al 1999), perifused pancreas (Sone, H. et al 1999) or perifused islets (Sone, H. et al 2000). This effect of biotin on insulin secretion also appears to be dose-dependent (Sone, H. et al 1999).…”
Section: Biotinmentioning
confidence: 88%
See 1 more Smart Citation
“…A positive effect of biotin on insulin secretion has been reported (RomeroNavarro, G. et al 1999;Sone, H. et al 2000;Sone, H. et al 1999;Vilches-Flores, A. et al 2009). Studies by our group (Romero-Navarro, G. et al 1999;Vilches-Flores, A. et al 2009) and others (Sone, H. et al 2000;Sone, H. et al 1999) have revealed that glucose-stimulated insulin secretion increases in response to acute exposure to pharmacological doses of biotin in either primary cultured islets (Romero-Navarro, G. et al 1999), perifused pancreas (Sone, H. et al 1999) or perifused islets (Sone, H. et al 2000). This effect of biotin on insulin secretion also appears to be dose-dependent (Sone, H. et al 1999).…”
Section: Biotinmentioning
confidence: 88%
“…We have found that biotin stimulates insulin and pancreatic glucokinase expression (Romero-Navarro, G. et al 1999), an enzyme that plays an important role in glucose homeostasis regulating insulin secretion in response to changes in blood glucose concentrations. Our group found that biotin concentrations of 10 to 1000 nM augmented glucokinase activity and mRNA abundance in cultured rat pancreatic islets (Romero-Navarro, G. et al 1999). A similar stimulatory effect on pancreatic glucokinase was observed in the insulinoma RIN 1046-38 cell line (Borboni, P. et al 1996).…”
Section: Biotinmentioning
confidence: 99%
“…In reference to the latter, biotin status has been shown to influence the expression of more than 2,000 human genes, at both the transcriptional and post-transcriptional levels (3, 30, 44). The affected genes include those that are critical for maintaining the differentiated phenotype of pancreatic beta cells, preservation of their mass (i.e., their proportion), and for insulin secretion (3,30,38,44). In reference to the latter, the vitamin has been shown to increases the expression of pancreatic and duodenal homeobox 1 (Pdx-1) (44), a critical transcription factor for the expression of insulin, and several genes involved in its synthesis and secretion by pancreatic beta cells (2).…”
mentioning
confidence: 99%
“…24,29). In reference to the latter, biotin status has been shown to influence the expression of more than 2,000 human genes, at both the transcriptional and post-transcriptional levels (3,30,44). The affected genes include those that are critical for maintaining the differentiated phenotype of pancreatic beta cells, preservation of their mass (i.e., their proportion), and for insulin secretion (3,30,38,44).…”
mentioning
confidence: 99%
See 1 more Smart Citation